Break the MBA admissions barrier : making it to the world's best business schools - Jain, Mohit (Pearson Education, Dorling Kindersley, 2008)
Break The MBA Admission Barrier: Making It To The World's Best Business Schools provides a simple yet comprehensive approach to coaching in the workplace. It uses a step-by-step process, and in addition, it explains many of the supporting skills su.